A proposal of spatial measurement of peer effect through socioeconomic indices and unsatisfied basic needs - Gregorio Giménez; Denisa Ciobanu; Beatriz Barrado (Economies, 2021)
This paper investigates peer effects in the academic achievement of Costa Rican students. Two measures of peer effects are used: (1) a measure of a schools' average socioeconomic status and (2) a measure of unsatisfied basic needs at district level. The estimation of a three-level hierarchical model allows us to deal with selection bias and unobserved heterogeneity. Results show that socioeconomic peer effect, both at school and district levels, positively and significantly correlates with academic achievement. An increase in one standard deviation in the socioeconomic index has the same effect on academic achievement as an additional year of schooling; two years if the improvement occurs in the index of unsatisfied basic needs. These results are robust for mathematics, reading and science. Results from quantile regression reveal that students with high academic achievement take greater advantages from studying in schools with higher socioeconomic status (mathematics and reading). Meanwhile, students with low academic achievement are the most affected by studying in poorer districts (mathematics and science). These results show the strong feedback between educational and social inequity and constitute a good example of how poverty traps can persist in developing countries.
Keywords: 330; academic achievement; Costa Rica; peer effect; PISA; poverty; socioeconomic status; unsatisfied basic needs